High-toughness quartz stone plate and preparation method thereof

CN118145914BActive Publication Date: 2026-10-09GUANGDONG OVERLAND CERAMICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410185198.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-19
Publication Date
2026-10-09
Estimated Expiration
2044-02-19

AI Technical Summary

Technical Problem

[0003]现有技术的人造石英石制品一般是由不饱和聚酯与石英砂填料构成,工艺成熟,但是传统石英石板材采用的不饱和聚酯树脂在潮湿的环境下吸水率较高,易发生变形,在低温、高温或者在骤冷骤热的环境中,或者长期使用中的外部撞击等,力学性能降低导致板材变脆,甚至炸裂

Benefits of technology

本发明所述的一种高韧性石英石板材及其制备方法,由改性四针状氧化锌晶须、邻苯二甲酸二丁酯、碳纤维粉、聚酯纤维复配而成的增韧助剂,同不饱和聚酯树脂、硅烷偶联剂等成分协同增益,改性四针状氧化锌的使用提高了各成分之间的相容性,邻苯二甲酸二丁酯、碳纤维粉、聚酯纤维的添加改进了原料之间的填充紧密度,使得石英石板材的力学性能得到改进,可以有效改善石英石板材的韧性,防止石英石板材开裂、变形。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a high-toughness quartz stone plate and a preparation method thereof. The high-toughness quartz stone plate comprises, by weight, 47-63 parts of inorganic material, 12-15 parts of unsaturated polyester resin, 5-11 parts of toughening auxiliary agent, 1-2 parts of accelerator, 1-5 parts of curing agent and 1-2 parts of silane coupling agent. The toughening auxiliary agent is compounded by modified four-needle zinc oxide whisker, dibutyl phthalate, carbon fiber powder and polyester fiber. The modified four-needle zinc oxide whisker and the silane coupling agent jointly improve the compatibility of the unsaturated polyester resin and other components. The addition of the dibutyl phthalate, the carbon fiber powder and the polyester fiber improves the filling density among raw materials, further improves the mechanical properties of the quartz stone plate, improves the toughness of the quartz stone plate, and prevents the quartz stone plate from cracking and deforming.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of artificial quartz stone slab processing technology, specifically to a high-toughness quartz stone slab and its preparation method. Background Technology

[0002] Artificial quartz stone is made by using unsaturated resin as a binder, combined with various natural stone powder, silica sand, glass powder and other inorganic materials, as well as appropriate additives and colorants. With its bright appearance and excellent scratch resistance and stain resistance, it is widely used in various decoration and renovation projects such as cabinets, bathrooms, and office floors.

[0003] Existing artificial quartz stone products are generally composed of unsaturated polyester and quartz sand filler, and the technology is mature. However, the unsaturated polyester resin used in traditional quartz stone slabs has a high water absorption rate in humid environments, making it prone to deformation. In environments with low or high temperatures, sudden temperature changes, or long-term external impacts, its mechanical properties decrease, causing the slabs to become brittle and even crack. Therefore, to meet market demands, researching a high-toughness quartz stone slab is currently a key research direction. Summary of the Invention

[0004] This invention first provides a high-toughness quartz stone slab and its preparation method. The toughening agent improves the filling density and compatibility between the components, improves the performance, and makes the quartz stone slab less prone to cracking and deformation, and has high toughness.

[0005] The present invention solves the technical problem by adopting the following technical solution: This invention provides a high-toughness quartz stone slab and its preparation method, characterized in that the high-toughness quartz stone slab comprises, by weight: 47-63 parts of inorganic materials, 12-15 parts of unsaturated polyester resin, 5-11 parts of toughening agent, 1-2 parts of accelerator, 1-5 parts of curing agent, and 1-2 parts of silane coupling agent.

[0006] Preferably, the high-toughness quartz stone slab comprises, by weight: 52-58 parts of inorganic materials, 13-14 parts of unsaturated polyester resin, 7-9 parts of toughening agent, 1.4-1.6 parts of accelerator, 2.4-3.6 parts of curing agent, and 1.4-1.6 parts of silane coupling agent.

[0007] Preferably, the high-toughness quartz stone slab comprises, by weight: 55 parts inorganic material, 13.5 parts unsaturated polyester resin, 8 parts toughening agent, 1.5 parts accelerator, 3 parts curing agent, and 1.5 parts silane coupling agent.

[0008] Preferably, the inorganic material is composed of particulate filler and powder filler in a weight ratio of 1:(0.41~0.47); wherein the particulate material has a particle size of 20~60 mesh, including 15~19 parts of quartz sand and 5~7 parts of glass particles; and the powder material is quartz powder with a particle size of 330~360 mesh.

[0009] Preferably, the unsaturated polyester resin is composed of polymethyl methacrylate resin, tetrachlorophthalic anhydride type unsaturated polyester resin and adipic acid type unsaturated polyester resin in a weight ratio of 1:(0.33~0.46):(0.52~0.64); wherein the viscosity of the unsaturated polyester resin is 900~1200 MPa·s.

[0010] Preferably, the toughening agent is composed of modified tetraneedle zinc oxide whiskers, dibutyl phthalate, carbon fiber powder and polyester fiber in a weight ratio of 1:(0.37~0.49):(0.41~0.55):(0.22~0.38).

[0011] Preferably, the method for preparing the modified tetraneedle-shaped zinc oxide whiskers includes the following steps: S11. Prepare a zinc nitrate solution with a concentration of 0.5~1.0mol / L, and add 3.5~5wt% polyvinylpyrrolidone; pour 12mol / L hydrochloric acid into a reaction vessel containing magnesium carbonate, close the reaction vessel, and stir until the reaction inside the reaction vessel is complete and pressure is formed; S12. Slowly pass the carbon dioxide obtained above into the prepared zinc nitrate solution and react for 24-32 hours. S13. Heat the vacuum resistance furnace to 600~1000℃, put the slurry obtained in step S2 into the furnace, seal the device, draw a vacuum, control the vacuum degree to 0.5~1MPa, react for 2~3h, after the reaction is completed, filter the suspension, wash with a small amount of water, and continuously evaporate at 0.2~0.5MPa to obtain pre-made zinc oxide whiskers. S14. In a nitrogen atmosphere, magnesium is ultrasonically atomized into magnesium powder of 100-200 mesh; the pre-made zinc oxide whiskers are surface-modified with 0.5wt% KH506 coupling agent. S15. The modified zinc oxide whiskers and magnesium powder are ultrasonically dispersed in water, transferred to a hydrothermal reactor, treated at 100~120℃ for 4~6 hours, then cooled to 35~45℃, the supernatant is poured off, and the precipitate is filtered and washed 3 times to obtain the modified tetraneedle-shaped zinc oxide whiskers.

[0012] Preferably, the accelerator is one or more of N,N-dimethylaniline, diethylaniline, and cobalt naphthenate.

[0013] Preferably, the curing agent comprises 7.1 to 9.5 parts of tert-butyl peroxide-2-ethylhexanoate, 1.3 to 3.7 parts of triethylamine and 0.8 to 1.8 parts of cumene hydrogen peroxide.

[0014] Preferably, the preparation method of the high-toughness quartz stone slab includes the following steps: S21. Set the reaction conditions in the reactor to a nitrogen atmosphere, a temperature of 70~90℃, and a pressure of 0.2~0.5KPa. Add unsaturated polyester resin, coupling agent, and accelerator to the reactor in sequence, and stir for 10~20 minutes at a speed of 180~320rpm to obtain the first mixture. S22. Add curing agent to the first mixture and stir evenly. Pour it into a mixing tank and mix with inorganic materials. Control the stirring speed to 360~400 rpm and stir for 8~12 minutes to obtain the second mixture. S23. Spread the second mixture evenly in the mold and perform vacuum vibration. Set the vacuum degree to -0.08~-0.1MPa, the vibration frequency to 40~50HZ, and the vibration time to 6~8min. After vibration, perform vacuum pressing to degas the mixture and use medium-temperature curing molding. The medium-temperature curing molding temperature is 90~110℃ and the curing time is 70~90min. S24. After curing, let it cool at room temperature before putting it into a thickness calibrating machine to calibrate its thickness. Then, sand the surface of the board to obtain the finished product.

[0015] The beneficial effects of this invention are: The present invention discloses a high-toughness quartz stone slab and its preparation method. The toughening agent is composed of modified tetraneedle zinc oxide whiskers, dibutyl phthalate, carbon fiber powder, and polyester fiber. It has a synergistic effect with unsaturated polyester resin, silane coupling agent, and other components. The use of modified tetraneedle zinc oxide improves the compatibility between the components. The addition of dibutyl phthalate, carbon fiber powder, and polyester fiber improves the filling density between the raw materials, thereby improving the mechanical properties of the quartz stone slab. It can effectively improve the toughness of the quartz stone slab and prevent cracking and deformation. Detailed Implementation

[0016] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to specific examples. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0017] Example 1. The high-toughness quartz stone slab of this embodiment includes, by weight, 47 parts of inorganic materials, 12 parts of unsaturated polyester resin, 5 parts of toughening agent, 1 part of accelerator, 1 part of curing agent, and 1 part of silane coupling agent.

[0018] The inorganic material in this embodiment is composed of particulate filler and powder filler in a weight ratio of 1:0.41; wherein, the particulate material has a particle size of 20 mesh and includes 15 parts of quartz sand and 5 parts of glass particles; the powder material is quartz powder with a particle size of 330 mesh.

[0019] The unsaturated polyester resin in this embodiment is composed of polymethyl methacrylate resin, tetrachlorophthalic anhydride type unsaturated polyester resin and adipic acid type unsaturated polyester resin in a weight ratio of 1:0.33:0.52; wherein, the viscosity of the unsaturated polyester resin is 900 MPa·s.

[0020] The toughening agent in this embodiment is composed of modified tetraneedle zinc oxide whiskers, dibutyl phthalate, carbon fiber powder and polyester fiber in a weight ratio of 1:0.37:0.41:0.22.

[0021] The method for preparing the modified tetraneedle-shaped zinc oxide whiskers in this embodiment includes the following steps: S11. Prepare a 0.5 mol / L zinc nitrate solution and add 3.5 wt% polyvinylpyrrolidone; pour 12 mol / L hydrochloric acid into a reaction vessel containing magnesium carbonate, close the reaction vessel, and stir until the reaction inside the reaction vessel is complete and pressure is formed; S12. Slowly pass the carbon dioxide obtained above into the prepared zinc nitrate solution and react for 24 hours; S13. Heat the vacuum resistance furnace to 600℃, put the slurry obtained in step S12 into the furnace, seal the device, draw a vacuum, control the vacuum degree to 0.5MPa, react for 2 hours, after the reaction is completed, filter the suspension, wash with a small amount of water, and continuously evaporate at 0.2MPa to obtain pre-made zinc oxide whiskers. S14. In a nitrogen atmosphere, magnesium is ultrasonically atomized into 100-mesh magnesium powder; the pre-made zinc oxide whiskers are surface-modified with 0.5wt% KH506 coupling agent. S15. The modified zinc oxide whiskers and magnesium powder are ultrasonically dispersed in water, transferred to a hydrothermal reactor, treated at 100°C for 4 hours, then cooled to 35°C, the supernatant is poured off, and the precipitate is filtered and washed 3 times to obtain the modified tetraneedle-shaped zinc oxide whiskers.

[0022] The accelerator in this embodiment is N,N-dimethylaniline.

[0023] The curing agent in this embodiment includes 7.1 parts of tert-butyl peroxide-2-ethylhexanoate, 1.3 parts of triethylamine and 0.8 parts of cumene hydrogen peroxide.

[0024] The method for preparing high-toughness quartz stone slabs in this embodiment includes the following steps: S21. Set the reaction conditions in the reactor to a nitrogen atmosphere, a temperature of 70℃, and a pressure of 0.2KPa. Add unsaturated polyester resin, coupling agent, and accelerator to the reactor in sequence, and stir for 10 minutes at a speed of 180rpm to obtain the first mixture. S22. Add curing agent to the first mixture and stir evenly. Pour it into a mixing tank and mix with inorganic materials. Control the stirring speed to 360 rpm and stir for 8 minutes to obtain the second mixture. S23. Spread the second mixture evenly in the mold and perform vacuum vibration. Set the vacuum degree to -0.08MPa, the vibration frequency to 40HZ, and the vibration time to 6min. After vibration, perform vacuum pressing to degas the mixture and use medium-temperature curing molding. The medium-temperature curing molding temperature is 90℃ and the curing time is 70min. S24. After curing, let it cool at room temperature before putting it into a thickness calibrating machine to calibrate its thickness. Then, sand the surface of the board to obtain the finished product.

[0025] Example 2. The high-toughness quartz stone slab of this embodiment includes, by weight, 63 parts of inorganic materials, 15 parts of unsaturated polyester resin, 11 parts of toughening agent, 2 parts of accelerator, 5 parts of curing agent, and 2 parts of silane coupling agent.

[0026] The inorganic material in this embodiment is composed of particulate filler and powder filler in a weight ratio of 1:0.47; wherein, the particulate material has a particle size of 60 mesh and includes 19 parts of quartz sand and 7 parts of glass particles; the powder material is quartz powder with a particle size of 360 mesh.

[0027] The unsaturated polyester resin in this embodiment is composed of polymethyl methacrylate resin, tetrachlorophthalic anhydride type unsaturated polyester resin and adipic acid type unsaturated polyester resin in a weight ratio of 1:0.46:0.64; wherein, the viscosity of the unsaturated polyester resin is 1200 MPa·s.

[0028] The toughening agent in this embodiment is composed of modified tetraneedle zinc oxide whiskers, dibutyl phthalate, carbon fiber powder and polyester fiber in a weight ratio of 1:0.49:0.55:0.38.

[0029] The method for preparing the modified tetraneedle-shaped zinc oxide whiskers in this embodiment includes the following steps: S11. Prepare a 1.0 mol / L zinc nitrate solution and add 5 wt% polyvinylpyrrolidone; pour 12 mol / L hydrochloric acid into a reaction vessel containing magnesium carbonate, close the reaction vessel, and stir until the reaction inside the reaction vessel is complete and pressure is formed; S12. Slowly pass the carbon dioxide obtained above into the prepared zinc nitrate solution and react for 32 hours. S13. Heat the vacuum resistance furnace to 1000℃, put the slurry obtained in step S12 into the furnace, seal the device, draw a vacuum, control the vacuum degree to 1MPa, react for 3 hours, after the reaction is completed, filter the suspension, wash with a small amount of water, and continuously evaporate at 0.5MPa to obtain pre-made zinc oxide whiskers. S14. In a nitrogen atmosphere, magnesium is ultrasonically atomized into 200-mesh magnesium powder; the pre-made zinc oxide whiskers are surface-modified with 0.5wt% KH506 coupling agent. S15. The modified zinc oxide whiskers and magnesium powder are ultrasonically dispersed in water, transferred to a hydrothermal reactor, treated at 120°C for 6 hours, then cooled to 45°C, the supernatant is poured off, and the precipitate is filtered and washed 3 times to obtain the modified tetraneedle-shaped zinc oxide whiskers.

[0030] The accelerator in this embodiment is N,N-dimethylaniline.

[0031] The curing agent in this embodiment includes 9.5 parts of tert-butyl peroxide-2-ethylhexanoate, 3.7 parts of triethylamine and 1.8 parts of cumene hydrogen peroxide.

[0032] The method for preparing high-toughness quartz stone slabs in this embodiment includes the following steps: S21. Set the reaction conditions in the reactor to a nitrogen atmosphere, a temperature of 90℃, and a pressure of 0.5KPa. Add unsaturated polyester resin, coupling agent, and accelerator to the reactor in sequence, and stir for 20 minutes at a speed of 320rpm to obtain the first mixture. S22. Add curing agent to the first mixture and stir evenly. Pour it into a mixing tank and mix with inorganic materials. Control the stirring speed to 400 rpm and stir for 12 minutes to obtain the second mixture. S23. Spread the second mixture evenly in the mold and perform vacuum vibration. Set the vacuum degree to -0.1MPa, the vibration frequency to 50HZ, and the vibration time to 8min. After vibration, perform vacuum pressing to degas the mixture and use medium-temperature curing molding. The medium-temperature curing molding temperature is 110℃ and the curing time is 90min. S24. After curing, let it cool at room temperature before putting it into a thickness calibrating machine to calibrate its thickness. Then, sand the surface of the board to obtain the finished product.

[0033] Example 3. The high-toughness quartz stone slab of this embodiment comprises, by weight: 55 parts inorganic material, 13.5 parts unsaturated polyester resin, 8 parts toughening agent, 1.5 parts accelerator, 3 parts curing agent, and 1.5 parts silane coupling agent.

[0034] The inorganic material in this embodiment is composed of particulate filler and powder filler in a weight ratio of 1:0.44; wherein, the particulate material has a particle size of 40 mesh and includes 17 parts of quartz sand and 6 parts of glass particles; the powder material is quartz powder with a particle size of 345 mesh.

[0035] The unsaturated polyester resin in this embodiment is composed of polymethyl methacrylate resin, tetrachlorophthalic anhydride type unsaturated polyester resin and adipic acid type unsaturated polyester resin in a weight ratio of 1:0.39:0.58; wherein, the viscosity of the unsaturated polyester resin is 1050 MPa·s.

[0036] The toughening agent in this embodiment is composed of modified tetraneedle zinc oxide whiskers, dibutyl phthalate, carbon fiber powder and polyester fiber in a weight ratio of 1:0.42:0.48:0.3.

[0037] The method for preparing the modified tetraneedle-shaped zinc oxide whiskers in this embodiment includes the following steps: S11. Prepare a zinc nitrate solution with a concentration of 0.8 mol / L and add 4.2 wt% polyvinylpyrrolidone; pour 12 mol / L hydrochloric acid into a reaction vessel containing magnesium carbonate, close the reaction vessel, and stir until the reaction inside the reaction vessel is complete and pressure is formed; S12. Slowly pass the carbon dioxide obtained above into the prepared zinc nitrate solution and react for 28 hours; S13. Heat the vacuum resistance furnace to 800℃, put the slurry obtained in step S12 into the furnace, seal the device, draw a vacuum, control the vacuum degree to 0.7MPa, react for 2.5h, after the reaction is completed, filter the suspension, wash with a small amount of water, and continuously evaporate at 0.35MPa to obtain pre-made zinc oxide whiskers. S14. In a nitrogen atmosphere, magnesium is ultrasonically atomized into 150-mesh magnesium powder; the pre-made zinc oxide whiskers are surface-modified with 0.5wt% KH506 coupling agent. S15. The modified zinc oxide whiskers and magnesium powder are ultrasonically dispersed in water, transferred to a hydrothermal reactor, treated at 110°C for 5 hours, then cooled to 35~45°C, the supernatant is poured off, and the precipitate is filtered and washed 3 times to obtain the modified tetraneedle-shaped zinc oxide whiskers.

[0038] The accelerator in this embodiment is N,N-dimethylaniline.

[0039] The curing agent in this embodiment includes 8.3 parts of tert-butyl peroxide-2-ethylhexanoate, 2.5 parts of triethylamine and 1.3 parts of cumene hydrogen peroxide.

[0040] The method for preparing high-toughness quartz stone slabs in this embodiment includes the following steps: S21. Set the reaction conditions in the reactor to a nitrogen atmosphere, a temperature of 80℃, and a pressure of 0.35KPa. Add unsaturated polyester resin, coupling agent, and accelerator to the reactor in sequence, and stir for 15 minutes at a speed of 250rpm to obtain the first mixture. S22. Add curing agent to the first mixture and stir evenly. Pour it into a mixing tank and mix with inorganic materials. Control the stirring speed to 380 rpm and stir for 10 minutes to obtain the second mixture. S23. Spread the second mixture evenly in the mold and perform vacuum vibration. Set the vacuum degree to -0.09MPa, the vibration frequency to 45HZ, and the vibration time to 7min. After vibration, perform vacuum pressing to degas the mixture and use medium-temperature curing molding. The medium-temperature curing molding temperature is 100℃ and the curing time is 80min. S24. After curing, let it cool at room temperature before putting it into a thickness calibrating machine to calibrate its thickness. Then, sand the surface of the board to obtain the finished product.

[0041] Comparative Example 1. Unlike Example 3, it does not contain toughening additives.

[0042] Comparative Example 2. The difference from Example 3 is that zinc oxide is used instead of modified tetraneedle zinc oxide whiskers.

[0043] Comparative Example 3. The high-toughness quartz stone slab differs from Example 3 in its composition, which is: This comparative example of a high-toughness quartz stone slab comprises, by weight: 55 parts inorganic material, 13.5 parts polymethyl methacrylate resin, 8 parts toughening agent, 1.5 parts accelerator, 3 parts curing agent, and 1.5 parts silane coupling agent.

[0044] Comparative Example 4. Unlike Example 3, the preparation method of the high-toughness quartz stone slab is different. S21. Add unsaturated polyester resin, coupling agent and accelerator to the mixing tank, and stir for 15 minutes at a speed of 250 rpm to obtain the first mixture. S22. Add curing agent to the first mixture and stir evenly. Then pour in inorganic material and mix. Control the stirring speed to 380 rpm and stir for 10 minutes to obtain the second mixture. S23. Spread the second mixture evenly in the mold and perform vacuum vibration. Set the vacuum degree to -0.09MPa, the vibration frequency to 45HZ, and the vibration time to 7min. After vibration, perform vacuum pressing to degas the mixture and use medium-temperature curing molding. The medium-temperature curing molding temperature is 100℃ and the curing time is 80min. S24. After curing, let it cool at room temperature before putting it into a thickness calibrating machine to calibrate its thickness. Then, sand the surface of the board to obtain the finished product.

[0045] The strength properties of the products from Examples 1-3 and Comparative Examples 1-4 of the present invention are shown in Table 1 below.

[0046] Table 1

[0047] As can be seen from Table 1, the components of the product of the present invention have a synergistic effect and excellent toughness properties.

[0048] As can be seen from Examples 1-3, the high-toughness quartz stone slab of the present invention is prepared by compounding toughening additives, unsaturated polyester resin and other components. The compounding and use of modified tetraneedle zinc oxide whiskers with dibutyl phthalate, carbon fiber powder and polyester fiber improves the compatibility and filling density between the components, improves the performance of the quartz stone slab, increases the toughness of the quartz stone slab, prevents the quartz stone slab from cracking and deforming, and effectively extends the service life of the quartz stone slab.

[0049] Comparing Example 3 with Comparative Examples 1-4, it can be seen that all components in this invention have played their roles. The absence of components or the replacement of materials will lead to a weakening of the product effect. In addition, the mixing of materials in the reaction vessel in the early stage of preparation, under controllable conditions such as pressure and temperature, allows the components to fully react and synergistically enhance each other, resulting in a more obvious product effect.

[0050] Based on the above-described preferred embodiments of the present invention, it should be noted that the technical scope of the present invention is not limited to the contents of the specification. For those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A high-toughness quartz stone slab, characterized in that, The high-toughness quartz stone slab comprises, by weight: 47-63 parts inorganic materials, 12-15 parts unsaturated polyester resin, 5-11 parts toughening agent, 1-2 parts accelerator, 1-5 parts curing agent, and 1-2 parts silane coupling agent. The toughening agent is composed of modified tetraneedle-shaped zinc oxide whiskers, dibutyl phthalate, carbon fiber powder, and polyester fiber in a weight ratio of 1:(0.37~0.49):(0.41~0.55):(0.22~0.38). The method for preparing the modified tetraneedle-shaped zinc oxide whiskers includes the following steps: S11. Prepare a zinc nitrate solution with a concentration of 0.5~1.0mol / L, and add 3.5~5wt% polyvinylpyrrolidone; pour 12mol / L hydrochloric acid into a reaction vessel containing magnesium carbonate, close the reaction vessel, and stir until the reaction inside the reaction vessel is complete and pressure is formed; S12. Slowly pass the carbon dioxide obtained above into the prepared zinc nitrate solution and react for 24-32 hours. S13. Heat the vacuum resistance furnace to 600~1000℃, put the slurry obtained in step S12 into the furnace, seal the device, draw a vacuum, control the vacuum degree to 0.5~1MPa, react for 2~3h, after the reaction is complete, filter the suspension, wash with a small amount of water, and continuously evaporate at 0.2~0.5MPa to obtain pre-made zinc oxide whiskers. S14. Under nitrogen atmosphere, magnesium is ultrasonically atomized into magnesium powder of 100~200 mesh; the pre-made zinc oxide whiskers are surface modified with 0.5wt% KH506 coupling agent. S15. The modified zinc oxide whiskers and magnesium powder are ultrasonically dispersed in water, transferred to a hydrothermal reactor, treated at 100~120℃ for 4~6h, then cooled to 35~45℃, the supernatant is poured off, and the precipitate is filtered and washed 3 times to obtain the modified tetraneedle-shaped zinc oxide whiskers. The inorganic material is composed of particulate filler and powder filler in a weight ratio of 1:(0.41~0.47); wherein the particulate filler has a particle size of 20~60 mesh and includes quartz sand and glass particles; the powder filler is quartz powder with a particle size of 330~360 mesh.

2. The high-toughness quartz stone slab according to claim 1, characterized in that, The high-toughness quartz stone slab comprises, by weight: 52-58 parts inorganic materials, 13-14 parts unsaturated polyester resin, 7-9 parts toughening agent, 1.4-1.6 parts accelerator, 2.4-3.6 parts curing agent, and 1.4-1.6 parts silane coupling agent.

3. The high-toughness quartz stone slab according to claim 1, characterized in that, The high-toughness quartz stone slab comprises, by weight: 55 parts inorganic materials, 13.5 parts unsaturated polyester resin, 8 parts toughening agent, 1.5 parts accelerator, 3 parts curing agent, and 1.5 parts silane coupling agent.

4. The high-toughness quartz stone slab according to claim 1, characterized in that, The unsaturated polyester resin is composed of polymethyl methacrylate resin, tetrachlorophthalic anhydride type unsaturated polyester resin and adipic acid type unsaturated polyester resin in a weight ratio of 1:(0.33~0.46):(0.52~0.64); wherein the viscosity of the unsaturated polyester resin is 900~1200 MPa·s.

5. A high-toughness quartz stone slab according to claim 1, characterized in that, The accelerator is one or more of N,N-dimethylaniline, diethylaniline, and cobalt naphthenate.

6. A high-toughness quartz stone slab according to claim 1, characterized in that, The curing agent includes tert-butyl peroxide-2-ethylhexanoate, triethylamine, and cumene hydrogen peroxide.

Citation Information

Patent Citations

  • High-strength man-made quartz plate and preparation method thereof

    CN103833265A

  • Artificial quartz stone plate having toughness and preparation method thereof

    CN107140877A